Effects of Dietary Coated Lysozyme on the Growth Performance, Antioxidant Activity, Immunity and Gut Health of Weaned Piglets - Xiangfei Xu; Pan Huang; Xuemei Cui; Xuefeng Li; Jiaying Sun; Quanan Ji; Qiang Wei; Yee Huang; Zhefeng Li; Guolian Bao; Yan Liu (MDPI AG, 2022)
The purpose of this study was to evaluate the effects of dietary coated lysozyme on growth performance, serum biochemical indexes, antioxidant activity, digestive enzyme activity, intestinal permeability, and the cecal microbiota in weaned piglets. In total, 144 weaned Large White × Landrace piglets were divided into six treatment groups, with 3 replicates and 8 piglets per replicate: CN, a basal diet; CL-L, CL-M, and CL-H, basal diet supplemented with 100, 150, 500 mg/kg coated lysozyme; UL, basal diet supplemented with 150 mg/kg lysozyme; and Abs, basal diet supplemented with 150 mg/kg guitaromycin for 6 weeks. Compared with the CN and UL diets, dietary CL-H inclusion increased the average daily gain (ADG) and decreased the feed/gain (F/G) ratio of piglets (p < 0.05). The addition of 500 mg/kg coated lysozyme to the diet significantly increased the total protein (TP) and globulin (Glob) plasma levels of weaned piglets (p < 0.05). Supplementation with 500 mg/kg coated lysozyme significantly increased the serum IgM concentration and increased lipase activity in the duodenum (p < 0.05). The addition of coated lysozyme and lysozyme significantly decreased the malondialdehyde (MDA) content, while the superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC) levels all increased (p < 0.05). High-throughput sequencing results showed that CL-H treatment effectively improved the intestinal microbiome. The relative abundance of Terrisporobacter in the CL-H and CL-M groups was significantly lower than that in the other groups (p < 0.05). LEfSe analysis results showed that the relative abundance of Coprococcus_3 was higher in the CL-M treatment group. The marker species added to the CL-H treatment group was Anaerofilum. In summary, as a potential substitute for feed antibiotics, lysozyme is directly used as a dietary additive, which is inefficient. Therefore, we used palm oil as the main coating material to coat lysozyme. Lysozyme after coating can more effectively improve the growth performance of piglets by improving the intestinal flora, improving the activity of digestive enzymes, reducing the damage to intestinal permeability and oxidative stress in piglets caused by weaning stress, and improving the immunity of piglets.